SOCIAL ENTREPRENEURSHIP AND NEOLIBERALISM making money while doing good. - BANDINELLI, CAROLINA (ROWMAN & LITTLEFIELD INTE, 2019)
Contemporary Western societies seem to be marked by a revival of ethics: virtually every actor claims to be doing something `good', or even to be willing to `change the world'. Social innovation, sharing economy and ethical business are just few of the tags attached to this manifold cultural trend, which is indicative of the attempt to reintegrate ethical responsibility with economic conduct. But how can entrepreneurship be redefined as the best way to express one's will to change society? How can people decide to actualise their desire to change how things are by means of a business? Social Entrepreneurship and Neoliberalism: Making Money While Doing Good tackles these questions, offering a critical yet empathetic account of the lifeworld of young social entrepreneurs in London and Milan.